Rapid humoral immune responses are required for recovery from haemorrhagic fever with renal syndrome patients. Issue 1 (1st January 2020) - Li, Yaoni; Quan, Chuansong; Xing, Weijia; Wang, Peihan; Gao, Jiming; Zhang, Zhenjie; Jiang, Xiaolin; Ma, Chuanmin; Carr, Michael J.; He, Qian; Gao, Lei; Bi, Yuhai; et al.
ABSTRACT : Haemorrhagic fever with renal syndrome (HFRS) following Hantaan virus (HTNV) infection displays variable clinical signs. Humoral responses elicited during HTNV infections are considered important, however, this process remains poorly understood. Herein, we have investigated the phenotype, temporal dynamics, and characteristics of B-cell receptor (BCR) repertoire in an HFRS cohort. The serological proﬁles were characterized by a lowered expression level of nucleoprotein (NP)-speciﬁc antibody in severe cases. Importantly, B-cell subsets were activated and proliferated within the first two weeks of symptom onset and moderate cases reacted more rapidly. BCR analysis in the recovery phase revealed a dramatic increase in the immunoglobulin gene diversity which was more significantly progressed in moderate infections. In severe cases, B-cell-related transcription was lower with inflammatory sets overactivated. Taken together, these data suggest the clinical signs and disease recovery in HFRS patients were positively impacted by rapid and efficacious humoral responses.